Extreme genetic mixing within colonies of the wood‐dwelling termite Kalotermes flavicollis (Isoptera, Kalotermitidae). Issue 12 (25th May 2013) - Luchetti, A.; Dedeine, F.; Velonà, A.; Mantovani, B.
Abstract The existence of altruism in social insects is commonly attributed to altruistic individuals gaining indirect fitness through kin selection. However, recent studies suggest that such individuals might also gain direct fitness through reproduction. Experimental studies on primitive wood‐dwelling termites revealed that colony fusion often causes the death of primary reproductives (queen and king), allowing opportunities for workers to inherit the nest by developing into replacement reproductives (neotenics). Therefore, colony fusion has been proposed as an important factor that may have favoured sociality in termites. However, whether colony fusion occurs frequently in natural populations of wood‐dwelling termites remains an open question. We analysed eleven colonies of the wood‐dwelling termite Kalotermes flavicollis (Kalotermitidae), using two mitochondrial and five nuclear microsatellite markers. Nine of eleven colonies (82%) were mixed families, with offspring of three or more primary reproductives. To our knowledge, this result represents the highest frequency of mixed‐family colonies ever reported in termites. Moreover, genetic mixing of colonies appeared extreme in two ways. First, the number of haplotypes per colony was exceptionally high (up to nine), indicating that colonies were composed of multiple queens' offspring. Second, some mixed‐family colonies included individuals belonging to two highly divergent genetic lineages. F‐statistics and relatedness values suggest that mixed‐family colonies most likely result from colony fusion, giving support to the accelerated nest inheritance theory. These findings raise important questions about the mode of foundation of mixed‐family colonies and the evolutionary forces that maintain them within populations.